Effects of social isolation on the cognitive status of people over 65 years of age during the SARS-CoV-2 pandemic: A longitudinal comparative study - Erick Miguel Fernández Jiménez; Alicia Zavala-Calahorrano; Aida Fabiola Aguilar Salazar (Medwave, 2023)
Introduction The SARS-CoV-2 pandemic has affected the entire population, especially vulnerable people with risk factors, such as people over 65 years. Globally and nationally, health protection measures were established to reduce transmission and the impact of the disease on the healthcare system, such as using face masks, hand washing, and social distancing, among others. This led to restrictions on activities outside the home, which affected the cognitive sphere of the population, especially people over 65 years of age.